Development of preschooler`s manual praxis with special educational needs during physical activity (power hand functions) - Moga Mykola (Науковий Вісник Південноукраїнського Національного Педагогічного Університету імені К. Д. Ушинського)
The article deals with the algorithm for forming manual praxis for children with special educational needs, particularly impaired psycho-speech development. The possibilities of wrist functions for preschool children as well as their systematization, classification, correction, and restoration of children’s practical development are highlighted. Based on the analysis of literary sources and personal experience of many years of observation, the importance of primary formation and correction of wrist functions in the general speech and physical development of preschoolers was determined. On its basis, it is necessary to build a wide arsenal of special exercises, and movement actions aimed at the formation of manual praxis, which includes three main categories of wrist functions: strength, coordination and speed. The connection of each category of wrist functions with the type of subject-practical activity relevant for a person (child) in the future social life is shown. These functions should be implemented in an ontogenetic sequence that reflects the physiological logic of building a child’s higher nervous activity. Special attention was paid to the support function of the upper limbs – it is the main one in the formation of the child’s musculoskeletal system. The classification of children’s wrist functions, special devices for wrist training, and specific examples of exercises for the formation of manual (wrist) praxis are also given. In the process of conducting a pedagogical experiment, the use of a common arsenal of manual general and purposeful actions, and physical exercises improves the development of wrist praxis, which positively affects the psycho-speech development of preschoolers with special educational needs.